Perkembangan dan Dinamika Pendidikan Islam di Malaysia: Analisis Historis dan Kontemporer - Adi Kusuma Pramesta (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This article provides a comprehensive overview of the development and contemporary dynamics of Islamic education in Malaysia. It traces the historical origins from the Malaccan Sultanate and the traditional pondok system to the structured madrasah model influenced by Middle Eastern graduates. The study analyzes the significant impact of British colonial policy and the post-independence state-driven centralization, which has progressively integrated Islamic education into the national curriculum. The article further examines the contemporary landscape, highlighting the roles of various types of schools, such as National Secondary Religious Schools (SMKA) and Community Religious Schools (SAR), and the government's policy of centralization. Key contemporary challenges are explored, including the need to balance Islamic values with globalization and digital transformation, the politicization of Islamic education between the ruling UMNO and the opposition PAS, and the imperative for curriculum modernization. The article argues that while Malaysia has been a pioneer in developing a robust and integrated Islamic education system, the future of the system lies in navigating the tensions between preserving its core Islamic identity and adapting to the challenges of modernity and technological change.